Negative magnetoresistance without well-defined chirality in the Weyl semimetal TaP - Arnold, Frank; Shekhar, Chandra; Wu, Shu-Chun; Sun, Yan; Dos Reis, Ricardo Donizeth; Kumar, Nitesh; Naumann, Marcel; Ajeesh, Mukkattu O.; Schmidt, Marcus; Grushin, Adolfo G.; Bardarson, Jens H.; Baenitz, Michael; et al. (Nature Communications, 2016)
Weyl semimetals (WSMs) are topological quantum states wherein the electronic bands disperse linearly around pairs of nodes with fixed chirality, the Weyl points. In WSMs, nonorthogonal electric and magnetic fields induce an exotic phenomenon known as the chiral anomaly, resulting in an unconventional negative longitudinal magnetoresistance, the chiral-magnetic effect. However, it remains an open question to which extent this effect survives when chirality is not well-defined. Here, we establish the detailed Fermi-surface topology of the recently identified WSM TaP via combined angle-resolved quantum-oscillation spectra and band-structure calculations. The Fermi surface forms banana-shaped electron and hole pockets surrounding pairs of Weyl points. Although this means that chirality is ill-defined in TaP, we observe a large negative longitudinal magnetoresistance. We show that the magnetoresistance can be affected by a magnetic field-induced inhomogeneous current distribution inside the sample.
CRIS-Team Scopus Importer:2023-03-20